Enhancing Students' Listening Skills: The Impact of the Innovative Ocean Application - Saktiono, Maxima ari; Saputra, Handika Diki; Prastiwi, Afita Dewi; Wahyudi, Moh. Rifqi Bagus (IJET (Indonesian Journal of English Teaching), 2025)
This study investigates the effectiveness of the Ocean application in enhancing listening skills among maritime students, a crucial competency in the maritime industry where clear and accurate communication can significantly impact safety and efficiency. The primary purpose of this research is to evaluate how the integration of auditory and visual stimuli within the Ocean application can improve students' ability to comprehend and retain maritime communication protocols. A mixed-method approach was employed in this study to provide a comprehensive analysis of the application's impact. The quantitative aspect involved pre- and post-assessment tests administered to a sample group of maritime students, measuring their listening skills before and after using the Ocean application. The qualitative aspect included interviews and surveys to gather user feedback on their experiences with the application, focusing on its usability, engagement, and perceived learning outcomes. The results of the study demonstrated a marked improvement in the listening skills of students who utilized the Ocean application. Quantitative data showed a statistically significant increase in test scores, indicating enhanced comprehension and retention of the material. Additionally, qualitative feedback from students highlighted the application's interactive features, such as synchronized audio-visual content, as particularly beneficial for maintaining engagement and reinforcing learning. Students reported that the application made complex maritime communication scenarios easier to understand and practice. These findings suggest that the Ocean application is an effective tool for enhancing listening skills in a maritime education context. The study concludes by recommending the broader adoption of such technology-driven learning tools in maritime training programs, emphasizing their potential to improve essential communication skills and overall safety in the industry.